TDIF overexpression in poplars retards internodal elongation and enhances leaf venation through interaction with other phytohormones. (19th December 2019) - Yue, Jing; Yang, Heyu; Yang, Shaohui; Wang, Jiehua
Abstract: As a member of the CLAVATA3 (CLV3)/EMBRYO SURROUNDING REGION-related (CLE) peptide family, tracheary element differentiation inhibitory factor (TDIF) plays crucial roles in vascular meristem maintenance by promoting cell proliferation and inhibiting xylem cell differentiation. In Populus trichocarpa, six TDIF-encoding genes are all expressed in vascular tissues, and in Arabidopsis PtTDIFpro:GUS lines, the expression driven by PtTDIF promoters were predominantly detected in stem vascular bundles, initiating leaves and leaf veins. Although exogenous application of two poplar TDIF peptides did not evidently affect the shoot growth in vitro, overexpression of PtTDIF genes in hybrid poplar severely retarded the internodal elongation by upregulating the expression of GA2ox and GA20ox genes and thus decreasing the level of endogenous gibberellins (GAs), which phenotypic defect could be rescued by exogenously applied GA3 . In addition, TDIF overexpression unexpectedly induced a more complex venation pattern in poplar leaves, which was underpinned by the elevated expression of WOX4 and WOX13 genes. Upon TDIF treatment, the DR5:GUS poplar leaves revealed a higher GUS activity and in TDIF -overexpressing leaves, the transcript abundances of several PIN-FORMED (PIN) genes, especially that of PIN1, were increased, which implied an integration of TDIF and auxin in mediating this process. Collectively, data of this work presented novel activities of TDIF involved in internode elongation and leaf vein formation, thus revealing the divergent functions of TDIF in perennial tree species from those in annual herbaceous Arabidopsis.